Teaching competencies needed in the education of children at the National Training School for Boys - Viernes, Nestor Ma. (Quezon City College of Education, University of the Philippines Diliman, 1977)
This paper provided some basic information on the need to assess and evaluate teacher performance with the view of improving classroom teaching. A modified competency checklist by Mackie, et. al. was administered to 25 SPED teachers at the National Training School for Boys to determine which competencies do they consider important in their work with socially alienated youth. Schwartz model of a clinical teacher served as basis for analysis of subject responses. Results obtained in the study would serve as a basis in determining competencies appropriate in the selection and recruitment of SPED teachers.
Thesis (Master of Arts in Teaching Special Education - Behavioral Porblems)--University of the Philippines, Diliman
Keywords: Special education teachers -- Training of -- Philippines -- Tanay (Rizal) -- Evaluation; Juvenile recidivists -- Philippines -- Tanay (Rizal); Special education -- Philippines -- Tanay (Rizal); Male juvenile delinquents -- Education -- Philippines